An Outcomes-Based Definition of Proteinuria Remission in Focal Segmental Glomerulosclerosis - Troost, Jonathan P; Trachtman, Howard; Nachman, Patrick H; Kretzler, Matthias; Spino, Cathie; Komers, Radko; Tuller, Sarah; Perumal, Kalyani; Massengill, Susan F; Kamil, Elaine S; Oh, Gia; Selewski, David T; et al. (Clinical journal of the American Society of Nephrology, 2018)
Proteinuria is used as an indicator of FSGS disease activity, but its use as a clinical trial end point is not universally accepted. The goal of this study was to refine proteinuria definitions associated with long-term kidney survival. Data on 466 patients with primary FSGS with proteinuria (urine protein-to-creatinine ratio >1 g/g) were analyzed from five independent cohorts. Proteinuria by months 1, 4, and 8 after study baseline was categorized by conventional definitions of complete (<0.3 g/g) and partial remission (<3.5 g/g and 50% reduction in proteinuria). Novel remission definitions were explored using receiver operating curves. Kaplan-Meier methods were used to estimate the associations of proteinuria with progression to ESRD or a 50% loss in kidney function. Propensity score-adjusted Cox proportional hazards models were used to adjust for baseline proteinuria, eGFR, and therapy. In the initial derivation cohort, conventional partial remission was not associated with kidney survival. A novel definition of partial remission (40% proteinuria reduction and proteinuria<1.5 g/g) on the basis of receiver operating curve analyses of 89 patients was identified (Sensitivity=0.70; Specificity=0.77). In the validation cohort analyses, complete remission was associated with better prognosis (6 out of 41 patients progressed to kidney failure; 6.6 per 100 patient-years) as was the novel partial remission (13 out of 71 progressed; 8.5 per 100 patient-years), compared with those with no response (51 out of 116 progressed; 20.1 per 100 patient-years). Conventional partial remission at month 8, but not month 4, was also associated with better response (19 out of 85 patients progressed; risk=10.4 per 100 patient-years). Propensity score-adjusted analyses showed the novel partial remission was associated with less progression at months 4 and 8 (month 4: hazard ratio, 0.50; =0.01; month 8: hazard ratio, 0.30; =0.002). Reaching either a complete or partial remission using a novel or conventional definition was associated with better long-term outcomes in patients with FSGS. This article contains a podcast at https://www.asn-online.org/media/podcast/CJASN/2018_02_20_CJASNPodcast_18_3_T.mp3.